Dampak Peran Ganda Petani Perempuan dalam Kehidupan Rumah Tangga di Masa Kini - Hamdani Thaha; Vera Yuniar (UIN Raden Mas Said Surakarta, 2023)
The dual role of women is the active involvement of women in the process of achieving goals based on independent personal abilities in deciding a goal. Women as wives for their husbands and as mothers of children is a status that has consequences for their role in family life, but sometimes that role does not function properly because it is accompanied by other roles as breadwinners, sometimes even that role becomes dominant to women's attention because it is related to family survival. The purpose of this study was to impact the dual role women to work as farmers in Gamaru Hamlet, Ulusalu Village, Latimojong District, Luwu Regency, South Sulawesi. This research is a type of qualitative research with a case study approach. Researchers obtained data through observation, interviews and documentation. The results of this study are four impacts experienced by women in carrying out their dual roles as farmers in Gamaru Hamlet, Ulusalu Village, Latimojong District, Luwu Regency, namely first Social Status, second Economic Impact, third Impact on family life, fourth Social Impact. The implications of the research are expected to be able to change people's views that domestic roles are not only women's affairs (wife) but also husband's affairs.